Development of Interactive Learning on Electric Charge Materials for Deaf Students - Nurkholifah, I Y; Mindyarto, B N; Astuti, B (Department of Physics, Faculty of Mathematics and Natural Sciences, 2022)
This study aims to develop learning media in the form of interactive videos and analyze the effectiveness of interactive science videos for deaf students. The method used is Research and Development by Sugiono, 2009. The subjects of this research trial were SMALB N Tegal students consisting of 8 students for small-scale trials and large-scale trials 10 students at SMALB N Semarang and SMALB Swadaya Semarang. the feasibility of the overall display as well as the content of the material and questions to measure the effectiveness of the learning media. The data analysis used was qualitative descriptive analysis and validated as well as video effectiveness analysis.Based on the data analysis of the validation results, it was shown that 73.75% was categorized as feasible and could be used in learning. The effectiveness data were analyzed using effect size and obtained a score of 2.16 on a small scale and 2.09 on a wide scale in the large category. Based on the results of the study, the media developed was suitable for use in the SMALB science learning process for deaf students.